1994
DOI: 10.1002/app.1994.070530307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water‐soluble polymers and aqueous‐phase viscosity on the interfacial tension behavior of reacting oil–alkaline systems

Abstract: SYNOPSISThis study presents the results of an experimental study of the effects of water-soluble polymer additives on the dynamic interfacial tension behavior of reacting oil-aqueous systems as measured by the spinning drop tensiometer. Polymer additives can exert both a direct physico-chemical effect and an indirect viscosity effect on the measured interfacial tension. This work, which complements a n earlier study dealing with the effects of oilsoluble polymer additives, reveals that the nominal effects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…4 Past research in this laboratory has focused on LS as an additive to PS in enhanced oil recovery. [5][6][7][8][9][10][11][12][13][14] Hornof studied the effect of adding LS to PS on interfacial tension (IFT) against various hydrocarbons. Their results showed that the largest reduction of IFT was observed with n-heptane, regardless of the surfactant formulations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Past research in this laboratory has focused on LS as an additive to PS in enhanced oil recovery. [5][6][7][8][9][10][11][12][13][14] Hornof studied the effect of adding LS to PS on interfacial tension (IFT) against various hydrocarbons. Their results showed that the largest reduction of IFT was observed with n-heptane, regardless of the surfactant formulations.…”
Section: Introductionmentioning
confidence: 99%
“…11 In another study, water-soluble polymer additives significantly influenced the dynamic IFT behavior of a reacting oil-water system as monitored by spinning drop tensiometer measurements. 14 IFT decreased as the concentration of water-soluble polymer [poly(vinyl alcohol) or polyacrylamide] additive increased in the case of linoleic acid in a paraffin oil mixture against distilled water, whereas the IFT increased as the concentration of water-soluble polymer additive increased in the case of linoleic acid in a paraffin oil mixture against aqueous NaOH solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation